2008
DOI: 10.1037/0735-7044.122.1.151
|View full text |Cite
|
Sign up to set email alerts
|

U-69593, a kappa opioid receptor agonist, decreases cocaine-induced behavioral sensitization in female rats.

Abstract: This study was designed to investigate if the kappa opioid system regulates the locomotor response to cocaine in the female rat and to determine if the effect is dependent on estradiol treatment. Adult rats were ovariectomized (OVX) and half received an estradiol (OVX-EB) implant. After a week, rats were injected for 5 consecutive days with vehicle or with the KOPr agonist U-69593 (0.16 mg/ kg, 0.32 mg/kg, 0.64 mg/kg) 15 min prior to cocaine injection (15 mg/kg). Following a 7 day drug free period, rats were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 62 publications
1
23
1
Order By: Relevance
“…One additional goal of substance abuse research involves identifying behavioral and pharmacological interventions that prevent or attenuate the development of sensitization to the behavioral effects of addictive drugs. Opioids have previously been shown to be effective at blocking the development of sensitization to cocaine (Heidbreder et al, 1993;Shippenberg et al, 1996;Puig-Ramos et al, 2008), and the present findings suggest that opioids may also be effective at preventing the development of sensitization to morphine and other agonists. As noted above, dysphoria and hallucinations limit the clinical utility of opioids in human populations, and the clinical utility of mixed / opioids is still a matter of debate.…”
Section: Downloaded Fromsupporting
confidence: 70%
See 1 more Smart Citation
“…One additional goal of substance abuse research involves identifying behavioral and pharmacological interventions that prevent or attenuate the development of sensitization to the behavioral effects of addictive drugs. Opioids have previously been shown to be effective at blocking the development of sensitization to cocaine (Heidbreder et al, 1993;Shippenberg et al, 1996;Puig-Ramos et al, 2008), and the present findings suggest that opioids may also be effective at preventing the development of sensitization to morphine and other agonists. As noted above, dysphoria and hallucinations limit the clinical utility of opioids in human populations, and the clinical utility of mixed / opioids is still a matter of debate.…”
Section: Downloaded Fromsupporting
confidence: 70%
“…Unlike that seen with morphine and buprenorphine, this effect was consistent across the 5 days of testing, and no progressive increase in locomotor activity was observed. Previous studies have revealed that agonists prevent the development of sensitization to the behavioral effects of cocaine (Heidbreder et al, 1993;Shippenberg et al, 1996;Puig-Ramos et al, 2008); however, their effects on the development of sensitization to morphine and other opioids are less clear. For instance, although an early study reported that the agonists U50488 and U69593 blocked the development of sensitization to morphine (Spanagel, 1995), a later study reported that U69593 did not block the development of sensitization to morphine or the development cross-sensitization to cocaine in morphine-treated animals (Shippenberg et al, 1998).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Furthermore, in the four core genotype mice U50,488H produced a slightly greater antinociception at 90 min post-treatment in the hot-plate test in XX neonates in comparison to XY neonates, independent of gonadal status (i.e., male or female) (Gioiosa et al, 2008), indicating that sex chromosomes affect KOPR responses. Lastly, acute treatment with U69,593 decreased acute cocaine-induced locomotor activity in ovariectomized females regardless of estradiol replacement (Puig-Ramos et al, 2008), indicating that ovarian hormones do not influence this KOPR effect.…”
Section: Discussionmentioning
confidence: 89%
“…Yet, very few studies have been conducted in females (Sershen et al, 1998;Puig-Ramos et al, 2008). Because the KOPR is significantly involved in regulating the effect of drugs of abuse, it is important to determine whether sex differences in this aspect of KOPR pharmacology exist.…”
Section: Introductionmentioning
confidence: 99%
“…The ef fect of ATPM-ET on morphine-induced behavioral sensitization It has been reported previously that behavioral sensitization is involved in opioid addiction and that κ-opioid agonists can attenuate many of the behavioral effects induced by opiates [21][22][23] . As a result, we decided to investigate the effects of ATPM-ET on morphine-induced behavioral sensitization.…”
Section: The Effect Of Atpm-et On Morphine Physical Dependencementioning
confidence: 99%